Muistelen Elvistä - Loukiala, Pekka, 1944-2010; Kurki, Eero ([Riihimäki] : Mellow, 1977)
12 kappaletta.
Can't help falling in love ; It's now or never ; Tell me that you love me ; I want you I need you I love you ; Stuck on you ; Don't be cruel // Love me tender ; Blue suede shoes ; Loving you ; Mean woman blues ; Don't ; Tutti frutti.
Pekka Loukiala (lauluääni), Eero Kurki yhtyeineen.